Rational design, synthesis, and evaluation of novel polypharmacological compounds targeting NaV1.5, KV1.5, and K2P channels for atrial fibrillation - Camargo-Ayala, Lorena; Bedoya, Mauricio; Dasí, Albert; Prüser, Merten; Schütte, Sven; Prent-Peñaloza, Luis; Adasme-Carreño, Francisco; Kiper, Aytuğ; Rinné, Susanne; Camargo-Ayala, Paola Andrea; Peña-Martínez, Paula A.; Bueno-Orovio, Alfonso; et al. (The journal of biological chemistry, 2025)
Atrial fibrillation (AF) involves electrical remodeling of the atria, with ion channels such as NaV1.5, KV1.5, and TASK-1 playing crucial roles. This study investigates acetamide-based compounds designed as multi-target inhibitors of these ion channels to address AF. Compound 6f emerged as the most potent in the series, demonstrating a strong inhibition of TASK-1 (IC50 ∼ 0.3 μM), a moderate inhibition of NaV1.5 (IC50 ∼ 21.2 μM) and a subtle inhibition of KV1.5 (IC50 ∼ 81.5 μM), alongside unexpected activation of TASK-4 (∼ 40% at 100 μM). Functional assays on human atrial cardiomyocytes from sinus rhythm (SR) and patients with AF revealed that 6f reduced action potential amplitude in SR (indicating NaV1.5 block), while in AF it increased action potential duration (APD), reflecting high affinity for TASK-1. Additionally, 6f caused hyperpolarization of the resting membrane potential in AF cardiomyocytes, consistent with the observed TASK-4 activation. Mathematical modeling further validated its efficacy in reducing AF burden. Pharmacokinetic analyses suggest favorable absorption and low toxicity. These findings identify 6f as a promising multi-target therapeutic candidate for AF management.